Formation of self-organized nano-dimensional structures on InP surfaces using ion irradiation and their wettability: A study based on experimental and theoretical concepts of surface. (October 2022) - Sulania, Indra; Kumar, Pravin; Priya, P.K.; Bhasker, H.P.; Singh, U.B.; Karn, Ranjeet K.; Tyagi, Chetna; Yadav, R.P.
Abstract: InP surfaces are bombarded with 50 keV Ar + ion beam at normal incidence with fluences ranging from∼2 × 10 16 to 8 × 10 16 ions/cm 2 . The formation of self-organized nanodots on Indium Phosphide (InP) are captured by Atomic Force Microscope (AFM) and Scanning Electron Microscope (SEM). Uniformity in size of dots is improved for the higher fluences and the surface becomes Indium rich with ion irradiation. Wettability studies show that the surface contact angle (CA) increases with ion irradiation and stabilizes for later fluences. The autocorrelation and height-height correlation function are applied for surface correlation and fractal nature of AFM images. Wetting properties of fractal surfaces are explored. The interface-width is found to increase with the ion fluences. The lateral correlation length is computed using auto-correlation function, while roughness exponent and the fractal dimension were estimated using height-height correlation function. Larger values of interface width indicate the larger self-organized nanodots on the surface. Fractal formations are able to capably disperse or collect mass, energy, and information over large spatial and temporal dimensions. Due to these properties, artificial fractal structures are becoming an essential and fundamental topic of study in applied research. Highlights: Formation of self-organized nanodots on InP surfaces upon bombarding these with 50 keV Ar + ion beam is reported. Surface becomes Indium rich with ion beam irradiation. Surface contact angle increases with ion irradiation and stabilizes at higher fluences. Theoretical simulations support formation of dots. Thus, wetting nature of any solid surface may be tuned by optimizing the ion beam parameters in a desired way.